Financial Literacy and Physician Wellness: Can a Financial Curriculum Improve an Obstetrician/Gynecologist Resident and Fellow's Well-Being? - Cawyer, Chase R.; Blanchard, Christina; Kim, Kenneth H. (American Journal of Perinatology Reports, 2022)
Objective This study aimed to evaluate the effects of a financial literacy curriculum on resident and fellow's sense of well-being and financial stress.Study Design This single institution pilot study prospectively enrolled obstetrician/gynecologist (OB/GYN) medical trainees (residents and fellows) to take part in a five-part personal financial literacy curriculum during the 2019 to 2020 academic year. Topics covered included the following: financial education and its relationship to personal well-being, overview of financial terms and principles, budgeting, debt planning, and investing and giving. Primary outcomes were the improvement in well-being as measured by the Expanded Well-Being Index (E-WBI) and financial stress as measured by the Financial Stress Scale-College Version (FSS-CV) survey.Results Of the 35 residents and fellows who participated in the study, 21 (60%) completed the postintervention survey. After course completion, there was significant improvement in the individual's E-WBI (p < 0.05) and no significant improvement in their FSS-CV (p = 0.06). After completing the course, trainees agreed that financial literacy improved their sense of well-being (p = 0.018).Conclusion Cultivating financial literacy is associated with an improvement in the sense of well-being in residents and fellows and should be considered for inclusion in other graduate medical education (GME) programs.
Keywords: physician burnout; personal financial planning; financial literacy; physician wellness